Approach to the Assessment and Management of Adult Patients With Atopic Dermatitis: A Consensus Document. Issue 1 (November 2018) - Gooderham, Melinda J.; Hong, Chih-ho; Albrecht, Lorne; Bissonnette, Robert; Dhadwal, Gurbir; Gniadecki, Robert; Grewal, Parbeer; Kirchhof, Mark G.; Landells, Ian; Lansang, Perla; Lynde, Chuck W.; Papp, Kim A.; et al.
Background: Atopic dermatitis (AD) is a chronic, relapsing, and remitting inflammatory skin disease with complex pathophysiology, primarily driven by type 2 inflammation. Existing guidelines often do not reflect all current therapeutic options and guidance on the practical management of patients with AD is lacking. Objectives: To develop practical, up-to-date guidance on the assessment and management of adult patients with AD. Methods: An expert panel of 17 Canadian experts, including 16 dermatologists and 1 allergist, with extensive clinical experience managing moderate-to-severe AD reviewed the available literature from the past 5 years using a defined list of key search terms. This literature, along with clinical expertise and opinion, was used to draft concise, clinically relevant reviews of the current literature. Based on these reviews, experts developed and voted on recommendations and statements to reflect the practical management of adult patients with AD as a guide for health care providers in Canada and across the globe, using a prespecified agreement cutoff of 75%. Results: Eleven consensus statements were approved by the expert panel and reflected 4 key domains: pathophysiology, assessment, comorbidities, and treatment. Conclusions: These statements aim to provide a framework for the assessment and management of adult patients with AD and to guide health care providers in practically relevant aspects of patient management.